THE RELEVANCE OF STUDYING FOREIGN LANGUAGES IN THE FIELD OF INTERNATIONAL ECONOMIC RELATIONS - Kamola Kayumova (Bright Mind Publishing, 2025)
This article analyzes the importance of learning foreign languages in modern society and personal development. The study of foreign languages is assessed not only as a means of communication, but also as an important factor in the development of cultural and intellectual skills. The article addresses the impact of learning foreign languages on global integration, professional success, scientific research and international cooperation. In addition, the difficulties that arise in the process of learning a foreign language and strategies to overcome them are also considered.
Keywords: Learning foreign languages, intercultural communication, intellectual development, global integration, educational strategies.